Pengaruh Lingkungan Kerja Fisik dan Kompensasi Terhadap Kepuasan Kerja Karyawan PT Bank Rakyat Indonesia (Persero) Tbk Cabang Rantepao Toraja Utara - Vivia Tandi Pailan; M. Ikhwan Maulana Haeruddin; Zainal Ruma; Tenri Sayu Puspitaningsih Dipoatmodjo; Rezky Amalia Hamka (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to determine the influence of physical work environment and compensation on employee job satisfaction. This research is a quantitative research with a descriptive approach. The sample in this study is 32 permanent employees at PT Bank Rakyat Indonesia (Persero) Tbk Rantepao North Toraja Branch. The data collection technique was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression analysis using Statictical Product Servive Solution (SPSS). The results of this study show that: 1) The physical work environment variable partially does not have a significant influence on employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Rantepao North Toraja Branch, 2) The compensation variable has a positive and significant influence on employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Rantepao North Toraja Branch, 3) the physical work environment variable and compensation simultaneously have a positive influence and significant to employee job satisfaction at Bank Rakyat Indonesia (Persero) Tbk Rantepao North Toraja Branch.